Level Of Teachers Awarness Of Their Roles In Counselling Secondary School Students For Skill Aquisition In Rivers State, South-South Nigeria: Management Perspective - Osaat, Dinah Sunday (Advances in Social Sciences Research Journal, 2020)
The study was designed to investigate level of teachers’ awareness of their roles in counselling secondary schools for skill acquisition in rivers state. The study adopted a descriptive survey design. The population of the study consist of 8196 (4436 males and 3760) females. A samples size of 450 teachers which was 5% of the population was selected being 222 males and 190 females, using the stratified random sampling technique. The instrument for data collection included a self constructed questionnaire’, which was based on a four point likert type scale of very high extent (4points), high extent (3 points) low extent (2 points) and very low extent. (1point).The mean and standard deviation were used to answer the research questions. Findings showed among others that the extent of teachers’ awareness of their roles in counselling secondary school students for skill acquisition in school is poor and this implies that the students are not exposed to adequate knowledge of the need for skill acquisition which will still lead to laziness and idleness of our graduates. The study therefore recommended among others that ; adequate training should be given to teachers of their roles as counsellors in secondary schools and enough time should be created for guidance and counselling programme in the school time table so that teachers can comfortably handle their clients